A textual analysis of Hasan Kenzi’s divan and the vezin–usul relationship in his musicalized poems - Küçükçalık, Bedia. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
The purpose of this study is to present the divan (collected poems) of Hasan Kenzi, a Sufi poet and musician who lived in the eighteenth century. In addition to a textual analysis, information about his life, works and his literary understanding are given in the thesis. After that, Hasan Kenzi’s divan was examined in the context of its religious and mystical elements. Another issue addressed in this thesis is the relevance of vezin (meter) and usul (tempo) in the musicalized poems of Hasan Kenzi. In the first part of the study, a textual analysis was done according to the single copy of the divan and poems that are not in the divan but which are compiled from various sources, with mecmuas (poetry magazine) appended at the end of the transcribed text. Information about his works and musician identity is given, based on the poet’s vakfiye (deed of trust of a pious foundation) records, which were found in Manisa, and tezkires (collection of biographies). To study the divan in terms of form and content, rhythm and rhyme features were first explored, after which religious and mystical elements in the poems were described. In the second part of the study, information is provided on Turkish religious music and general developments in this field in the eighteenth century. Subsequently, the relationship of vezin and usul, was evaluated from different perspectives as reported by various researchers. Finally, the reasons for using certain usuls to musicalize poems written with certain aruz (prosody) meters have been investigated.
Keywords: Turkish poetry.; Musicians -- Turkey.